2020
DOI: 10.1109/tse.2018.2842201
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Satisfaction of Software Engineers

Abstract: Context: The proper management of people can help software organisations to achieve higher levels of success. However, the limited attention paid to the appropriate use of theories to underpin the research in this area leaves it unclear how to deal with human aspects of software engineers, such as motivation and satisfaction. Objectives: This article aims to expose what drives the motivation and satisfaction of software engineers at work. Methods: A multiple case study was conducted at four software organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 76 publications
(91 reference statements)
0
45
1
1
Order By: Relevance
“…It seems that little research on the measurement of human values in SE exists. ESEM research focusing on human factors [1,4,9,14,15] differs from ours in terms of approach and thematic focus.…”
Section: Measuring Values and Subjectivity In Sementioning
confidence: 79%
See 1 more Smart Citation
“…It seems that little research on the measurement of human values in SE exists. ESEM research focusing on human factors [1,4,9,14,15] differs from ours in terms of approach and thematic focus.…”
Section: Measuring Values and Subjectivity In Sementioning
confidence: 79%
“…Thematic focus -research that investigates software practitioners' subjective views tends to focus on productivity [11] skills [9], and work motivation and satisfaction [4] [15]. Such research is often motivated by a desire to improve software engineers' working practices and foster more productive workplaces [15].…”
Section: Measuring Values and Subjectivity In Sementioning
confidence: 99%
“…More recently, Sach et al [13] analyzed data from interviews with 13 professional software engineers and suggested that there has been a trend toward more sociallyoriented motivators in software engineering. Other works, such as Franca et al [14], found a variety of factors that influence work motivation and job performance in the software industry.…”
Section: Rq1a: What Motivates Contributors To Oss Today? Rq1b: How Has Motivation To Contribute Shifted As Oss Has Matured?mentioning
confidence: 98%
“…The interviews included questions of two types. The first set of questions, which are not reported here, examined aspects of the interviewee's career, drawing on theory related to motivation [32] [12]. The last portion of each interview was spent discussing the interviewee's attitudes and beliefs about security and secure software development in the organization.…”
Section: A Data Collectionmentioning
confidence: 99%